Fostering Social Harmony and Minimizing Conflict Among Multi-ethnic Students Through Education in Semarang City - Mardiyati, Sofi; Suharini, Erni; Tri Atmaja, Hamdan (Journal of Educational Social Studies, 2024)
Indonesia is characterized by a pluralistic society, encompassing a wide range of ethnicities and religions. Effectively managing this diversity is essential for fostering harmony and minimizing conflicts. One of the principal mechanisms for achieving this is through education. This study investigates the management of multi-ethnic students at SMA Masehi 2 PSAK Semarang, focusing on social interactions and conflict resolution. Employing a qualitative phenomenological approach, the research explores the integration of multicultural education across intra-curricular, co-curricular, and extracurricular activities, as well as students' interpretations of multicultural values. Data were collected through in-depth interviews, observations, and documentation, and analyzed utilizing Herbert Blumer's Symbolic Interactionism Theory. The findings indicate that educational institutions play a pivotal role in facilitating the understanding and appreciation of diversity by promoting positive interactions and respect for cultural differences among students. Furthermore, schools actively endeavor to prevent and manage conflicts, thereby minimizing discord. The originality of this research lies in its exploration of structured multicultural education within schools, contributing to both social harmony and educational advancement in Indonesia. These findings offer broader implications for national education strategies aimed at fostering social cohesion.